2012
DOI: 10.1007/s12311-011-0339-1
|View full text |Cite
|
Sign up to set email alerts
|

RORalpha, a Key to the Development and Functioning of the Brain

Abstract: Studies of staggerer mice, in which retinoid-related orphan receptor-alpha (RORα) is mutated, have provided new insights into the critical functions of RORα in various physiological processes in peripheral tissues and in the brain. Staggerer mice present an ataxic phenotype caused by a massive neurodegeneration in the cerebellum. As a result, most of studies have focused on the role of RORα in the development of the cerebellum. Recent studies have expanded the role of RORα to other structures and functions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…have been posited. For example, Miller and colleagues (Miller et al 2013) referenced evidence of the role of RORA in protection against neurodegeneration in the face of oxidative stress (Jolly et al 2012). They hypothesized that RORA could modify neurodegeneration and functional abnormalities in areas of the brain associated with PTSD and related psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…have been posited. For example, Miller and colleagues (Miller et al 2013) referenced evidence of the role of RORA in protection against neurodegeneration in the face of oxidative stress (Jolly et al 2012). They hypothesized that RORA could modify neurodegeneration and functional abnormalities in areas of the brain associated with PTSD and related psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the cerebellum, RORα is expressed in other brain regions although its role there remains less studied. In addition to neurons, glial cells, particularly astrocytes, have been found to express RORα, possibly to regulate inflammatory and oxidative pathways (Jolly et al, 2012). New animal models with time-, cell type and region-dependent manipulations of RORα are needed to better appreciate the possible multiple roles of the gene.…”
Section: Animal Models Of Cerebellum Dysfunctionmentioning
confidence: 99%
“…Additionally, it has been shown that RORα is an important molecular player in diverse pathological processes including oxidative stress-induced apoptosis and cerebral hypoxia, both in neurons and astrocytes, due to its neuroprotective properties [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using staggerer mice, which have a 122 bp deletion in the RORα gene, allowed the identification of several functions of this nuclear receptor, both in the periphery and in the CNS. Interestingly, a massive cerebellar neurodegeneration leading to severe ataxia was also observed in these mice [ 44 ].…”
Section: Clock Genes In Glial Cellsmentioning
confidence: 99%